Original paperProlidase activity in chronic plaque psoriasis patients - Sürücü, Hacer Altın; Aksoy, Nurten; Ozgöztas, Orhan; Sezen, Hatice; Yesilova, Yavuz; Turan, Enver (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Psoriasis is a chronic, inflammatory, T-cell-mediated and hyperproliferative skin disease characterized by erythematous, squamous, sharply circumscribed and infiltrated plaques. The metabolisms of the collagen proteins undergo considerable changes due to the acceleration of their turnovers as a result of increased prolidase activity in psoriasis patients. Aim : To determine the level of prolidase activity in psoriasis patients and evaluate its relationship with the oxidative system. Material and methods The serum prolidase enzyme activity, total antioxidant levels and total oxidant levels of 40 psoriasis patients and a control group including 47 healthy individuals were analyzed by using their serum samples, and their oxidative stress indices were calculated. Results: The prolidase levels (p < 0.01), total oxidant levels (p < 0.01) and oxidative stress index levels (p < 0.001) of the patient group were higher than the corresponding parameters in the control group. The total antioxidant level was low (p < 0.01). Although a positive correlation was found between the prolidase and total antioxidant levels and the total oxidant level, no correlation was found between prolidase and the oxidative stress index. Conclusions : It has been determined that the activity of the prolidase enzyme increases due to the increased collage turnover in psoriasis patients. Increased serum oxidant levels and oxidative stress indices values may play a role in the pathogenesis of psoriasis.